Relationship between Intensity of Program Socialization by Managers and the Involvement of Learning Citizens in the Ar-Raudah PKBM - Anisa Nofriani; Vevi Sunarti (Universitas Negeri Padang, 2020)
The background of this research is that the lack of involvement of educated citizens in participating in the PKBM Ararudah PKBM Village in Pariaman City, the researchers suspect the cause of the lack of involvement of the learning community is due to the lack of intensity of program socialization by the manager. This study aims to find a picture of the intensity of program socialization by managers, knowing the picture of learning community involvement, and how the two are related. This type of research is quantitative research with a correlational approach. The study population was all learning residents who were active in the Ar-Raudah PKBM Balai Naras Village, Pariaman City, amounting to 43 people. The samples in this study were taken as much as 80% with a total of 35 people sampled. Data collection techniques in the form of a questionnaire with a data collection tool in the form of a questionnaire. Data analysis techniques in this study used the percentage formula and product moment. The results showed that: (1) the intensity of program socialization by managers is still lack, (2) the involvement of learning citizens is still low, and (3) there was a significant relationship between the intensity of program socialization by managers with the involvement of learning residents in PKBM Ar- Raudah in Balai Naras Village, Pariaman City.Keywords: Socialization Intensity, Involvement, Learning Citizens